South-East Asian Countries Defense Diplomacy Strategy for Capacity Building Study Case of Philipines - Putra, Calvin Anthony; Anwar, Syaiful; Duarte, Editha Praditya (Innovative: Journal Of Social Science Research, 2024)
This study explores the changing dynamics of defense and diplomacy in the Philippines amidst the escalating rivalry between the United States (US) and China. Due to its strategic geographical location, the Philippines faces susceptibility to the consequences of this rivalry. The primary focus is on the Philippines' comprehensive defense diplomacy strategy, which has been in practice since the Ramos administration. Rooted in the United Nations Convention on the Law of the Sea (UNCLOS), the Philippines pursues a law-centric diplomacy, notably through the 2009 Philippine Baselines Law. The strategic framework draws inspiration from Harry R. Yarger's "Little Book on Big Strategy," emphasizing the importance of aligning national strengths with the prevailing strategic environment. Actively engaging in capacity-building initiatives within Southeast Asia, the Philippines participates in various forums such as ASEAN, ADMM, and ADMM-Plus. These initiatives encompass the modernization of defense forces, increased maritime awareness, and fortified coastal defense. The discussion also encompasses the country's defense industry, the crucial role of the Armed Forces, and its readiness for international collaboration. In essence, the Philippines adopts a proactive approach by integrating diplomatic strategies, capacity-building endeavors, and a commitment to international law to ensure stability and security amidst evolving regional challenges.